Remote server telegram bot using long polling method at PT. Ngampooz Pintar Sejahtera - Irawan Irawan; Muhammad Ainur Rony; Motika Dian Anggraeni; Suwaebatul Aslamiyah (Jurnal Mantik, 2023)
Visibility is an important aspect of server management. A system administrator needs to have visibility into the servers under his management. A system administrator needs to have a vision of the current conditions on the servers under his control. With this visibility, you can see whether there is a problem with the server, and action can be taken to deal with the problem. One of the problems that occurs in companies or institutions that have servers to run public services is the lack of flexibility in the supervision process to continuously monitor server performance and condition 24 hours a day. Seeing these problems, it is necessary to have a system that can carry out monitoring and management remotely to increase the flexibility of system administrators. Telegram, which is a messaging platform, can be used as a remote management medium by utilizing the available bot features. The method used to communicate with the bot is the long polling method which is more efficient than the regular polling method. Using remote management via Telegram bot media can be an alternative way that system administrators can use to interact with the server. With this research, it is hoped that more efficient and flexible media or other methods can be developed for managing and monitoring servers